Comanagement in Maine: Integrating Fishermen’s Ecological Knowledge into Government Oversight of Fisheries - Hayden, Anne (Maine Policy Review, 2023)
Comanagement is the sharing of responsibility for management between fishermen and fisheries agencies. It shifts fishermen’s incentives to include longer term conservation goals, generates fine-scale information for management that would not otherwise be available, and develops fishing strategies that are consistent with conservation. Analysis of comanaged fisheries in Maine, for lobster, clams, river herring, and scallops, indicates that comanagement improves fisheries productivity and is more effective than standard, top-down, broad-scale fisheries management.